Brazing of SiC ceramics pretreated by chromium coating using inactive AgCu filler metal. Issue 6 (19th August 2020) - Chen, Zubin; Hu, Shengpeng; Song, Xiaoguo; Lei, Yu; Wang, Xinyuan; Long, Weimin; Feng, Jicai
Abstract: In this work, chromium coating conducted by magnetron sputtering was introduced to braze SiC ceramics using inactive AgCu filler metal. The results showed that reliable metallurgical bonding of SiC ceramics was obtained at 900°C for 10 minutes. SEM, XRD, and TEM were used to identify the reaction phase in the joint, and the typical interfacial microstructure was SiC/mixed CrSi2 + Cr23 C6 layer/CrSi2 /Ag(s, s)+Cu(s, s)/CrSi2 /mixed CrSi2 + Cr23 C6 layer/SiC. The shear strength of SiC joint using chromium coating brazed with inactive AgCu filler metal was 29.6 MPa and the joint fractured at the SiC substrate entirely after shear test. The proposed active element coating method provides a feasible way to achieve the brazing of ceramics.